THE EFFECT OF COMPETITIVE STRATEGIES ON THE PERFORMANCE OF CONSTRUCTION ORGANIZATIONS IN INDONESIA - Muji Indarwanto; Sarjono Puro; Edison H. Manurung (SINERGI, 2019)
This study was aimed at examining the effect of competitive strategies and performance of construction organizations in the large construction industry in Indonesia. This study adopted a quantitative research approach using a questionnaire survey to obtain data from 260 senior managers and CEOs of enormous construction organizations in Indonesia. Using Partial Least Square (PLS), we examined the relations between the constructs discussed in the study. We found out that competitive strategies affected the performance of construction organizations; competitive strategies positively impacted on the organizational performance. These findings showed that we needed to harmonize a competitive strategy as a prerequisite to achieving superior performance. We believed that this study positively contributed to the role of competitive strategy and the performance of large construction organizations in Indonesia and ongoing discussions on issues arising in construction management in development.